Da crítica ao simbólico: a reconstrução da objetividade em Kant e Cassirer - Souza, Vitor Hugo Oliveira (2025)
This study focuses on the epistemological analysis of Kant and Cassirer, aiming to understand the changes that make Cassirer’s philosophy distinct from Kant's. We develop an argument on the problem of objectivity, highlighting the transition from critical philosophy to the philosophy of symbolic forms, in relation to changes in the Faktum of science. This work aims to present to the reader: i) The change in objectivity that is constituted in scientific thought from the 17th to the 20th century. ii) The idealist stance in its neo-Kantian aspect, specifically Cassirer's stance. In the first stage, the foundations of the problems addressed by Cassirer and Kant are presented, focusing on objectivity and establishing the basis for analyzing Kant's thought in the context of the Enlightenment. Next, the construction of objectivity in Kant is explored, highlighting the influence of Cartesian metaphysics and Locke's epistemology in shaping his philosophical vocabulary. Additionally, the critique of innatism and the structure of rationalism are discussed. Finally, the third stage delves into the conception of objectivity in the philosophy of Ernst Cassirer, drawing from the influences of the Marburg Neo-Kantianism. At this point, the role of science, functional logic, and the concept of symbol in structuring his thought are analyzed.